A chemo-thermo-mechanically constitutive theory for thermal barrier coatings under CMAS infiltration and corrosion. (December 2019) - Xu, G.N.; Yang, L.; Zhou, Y.C.; Pi, Z.P.; Zhu, W.
Highlights: Constitutive theory is proposed for describing the high temperature CMAS corrosion process in thermal barrier coatings. Infiltration of CMAS and deformational behavior of corroded thermal barrier coatings are captured by both model and experiment. Out-plane tensile stress perpendicular to interface piles up under the corroded area. The mutual coupling effects of dissolution corrosion of YSZ, infiltration of CMAS and swelling deformation of coating have been discussed. Abstract: High temperature ceramic corroded by calcium-magnesium-alumino-silicates (CMAS) deposits is an inevitable part of severe degradation of thermal barrier coatings (TBCs). Based on thermodynamic laws, a mechanism-based constitutive theory is proposed for describing CMAS corrosion process at high temperature in TBCs. Concentration of metal cations in CMAS and degree of corrosion dissolution of TBCs are defined respectively. The constitute of free energy which decides the driving force for governing equation of field variables includes energy contribution from the infiltration of CMAS, the subsequent corrosion dissolution of TBCs by CMAS and elastic strain energy. Also, some coupling terms are added to the expression of free energy to describe coupled effects between field variables. We further establish two 3D plate models for TBCs with and without constraint by substrate to predict the chemo-mechanical response of corroded TBCs. A corrosion experiment is conducted to confirm deformational behavior of corroded TBCs and transient distribution of CMAS mass density. In addition, coupled kinetics capture that out-plane tensile stress piles up near the bottom of corroded coating with constraint by substrate, and disastrous delamination can occur from the interface under the CMAS covered region. The constitutive theory presented here provides a great potential for modeling chemo-thermo-mechanical corrosion process in TBCs at high temperature.